Haptic Training Simulation - Lelevé, Arnaud; McDaniel, Troy; Rossa, Carlos (Frontiers in Virtual Reality, 2020)
Immersive virtual environments combined with haptic (kinaesthetic and/or tactile) feedback are becoming an essential building block of simulator training in a variety of applications. This paper aims to illustrate the interest of hands-on training simulation with haptic feedback. We review the recent application domains and we expose the progress and open challenges in the medical domain which is particularly demonstrative. The paper then addresses two aspects of haptic feedback that could help enhance modern haptic training simulators' performance, namely transparent and efficient actuation for kinaesthetic feedback and tactile feedback. This research topic, beyond technological progress, should help design kinaesthetic and tactile haptic interfaces and motivate the use of new actuation techniques for more realistic and effective feedback in simulations as soon as users are immersed in virtual environments.